A capoeira na roda da escola e seu jogo com as ambivalências, as contingências, as incertezas e os conflitos - Penha, Vinícius (2009)
The objective of this dissertation is to investigate the Capoeira process insertion, a bodily cultural movement manifestation, in the school context, approaching the following subjects as research guides: How Capoeira goes into the schools? What are the impacts that Capoeira suffers to become a dimension of a true culture in the school context? The answers of this questions are linked to discussions related to the school, the culture, the physical education and Capoeira, having as methodology of research, the field work with beliefs of a qualitative research, involving cases like ethnographycal “type”. In this way, two elementary schools located in Serra City, Espírito Santo State, were chosen as a research field for this work development; During a visit to one of this school was possible to observe not just the Capoeira’s classes through the Capoeira shop, but also the physical education classes, approaching its school context insertion process, considering a school that works based on beliefs of a solid modernity, therefore, having as target to establish and keep the order. Along this work, will be related about this objectives problems, mainly in the established relations between the Capoeira and the physical education. In another school, the observation was centered only at the Capoeira shop, because it inserts itself in the school through sport. We reinforce that in both school, the Capoeira shop performs through a federal government program, called Programa Escola Aberta. It will be described about the problems related to the way to define what Capoeira is. However, there is not purpose to state the Capoeira insertion model in school context, but to know one of the ways that Capoeira was inserted in a determined school context. In this way, we investigated how Capoeira is approached in the schools and how its agents deal with the ambiguities, the uncertainties, the contingencies and the existing conflicts in the school context that must be considered as positives points in the education process, once that they allow to increase the knowledge production possibilities.